Determination of the total petroleum hydrocarbons in aquatic products by fluorescence spectrophotometry. Issue 5 (April 2020) - Ye, Hongli; Tian, Liangliang; Shi, Yongfu; Yu, Huijuan; Cai, Youqiong; Xi, Yanfeng; Tang, Yunyu; Zhang, Zhengquan; Huang, Dongmei
Abstract: The paper studied the determination of total petroleum hydrocarbon (TPHs) in aquatic products by fluorescence spectrophotometry method. To be suitable for the detection of TPHs in various aquatic products, the pretreatment conditions of the approach were optimized, such as the saponification temperature, saponification time, the adding order of anhydrous ethanol, the addition amount of extraction agent. The established method showed a good linearity in the TPHs range 0.0 ∼ 40.0 μg/mL (R 2 = 0.9965) with the limit of detection (LOD) 1.36 μg/mL and the precision of 6.1 % (relative standard deviation, RSD). The addition standard recoveries were 72.8 % ∼ 88.4 %. Finally, the method was successfully applied in detection of TPHs in the various aquatic products.